1-Deoxynojirimycin in Mulberry (Morus indica L.) Leaves Ameliorates Stable Angina Pectoris in Patients With Coronary Heart Disease by Improving Antioxidant and Anti-inflammatory Capacities - Ma, Yan; Lv, Wei; Gu, Yan; Yu, Shui (Frontiers in Pharmacology, 2019)
Objective Stable angina pectoris (SAP) in patients with coronary heart disease (CHD) and blood stasis syndrome (BSS) is a potentially serious threat to public health. NF-κB signaling is associated with angina pectoris. 1-Deoxynojirimycin (DNJ), which is a unique polyhydroxy alkaloid, is the main active component in mulberry (Morus indica L.) leaves and may exhibit protective properties in the prevention of SAP in patients with CHD by affecting the NF-κB pathway. Methods DNJ was purified from mulberry leaves by using a pretreated cation exchange chromatography column. A total of 144 SAP patients were randomly and evenly divided into experimental (DNJ treatment) and control (conventional treatment) groups. Echocardiography and ascending aortic elasticity were evaluated. The changes in inflammatory, oxidative, and antioxidant factors, including C-reactive protein (CRP), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), superoxide dismutase (SOD), and malondialdehyde (MDA), were measured before and after a 4-week treatment. Self-Rating Anxiety Scale (SAS) and Hamilton Depression Scale (HAMD) scores were compared between the two groups. The improvement in SAP score, associated symptoms, and BSS was also investigated. The levels of IkB kinase (IKK), nuclear factor-kappa B (NF-κB), and inhibitor of kappa B α (IkBα) were measured by Western blot. Results After the 4-week treatment, DNJ increased left ventricular ejection fraction and reduced left ventricular mass index, aortic distensibility, and atherosclerosis index (p < 0.05). DNJ intervention increased angina-free walking distance (p < 0.05). DNJ significantly reduced the levels of hs-CRP, IL-6, TNF-a, MDA, SAS, HAMD, AP, and BSS scores and increased SOD level (p < 0.05). The total effective rate was significantly increased (p < 0.05). The symptoms of angina attack frequency, nitroglycerin use, chest pain and tightness, shortness of breath, and emotional upset were also improved. DNJ reduced IKK and NF-κB levels and increased IkBα level (p < 0.05). Conclusions The DNJ in mulberry leaves improved the SAP of patients with CHD and BSS by increasing their antioxidant and anti-inflammatory capacities.